Carbon Offset: A Sustainable Green Mining Industry from the Triple Bottom Line Perspective - Widiarto, Rikha; Juanda, Ahmad; Leniwati, Driana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to develop a sustainable green mining model based on the Triple Bottom Line (TBL) framework, emphasizing that coal mining companies must not only focus on economic efficiency but also on reducing carbon emissions through natural-based offsets and social-environmental contributions. By using a qualitative case study approach on coal mining companies in Indonesia, this research highlights the urgency of integrating green practices into mining operations to address ecological damage and improve corporate sustainability reporting. This study employed a qualitative case study approach on a coal mining company group in Indonesia, involving eight key informants across various departments, utilizing participant observation, in-depth interviews, and document analysis, with data analyzed through reduction, linkage to the triple bottom line theory, and triangulation to ensure validity. This study concludes that green mining, when viewed through the triple bottom line lens economic, environmental, and social is an urgent and essential strategy for sustainable mining operations. Carbon offset mechanisms, such as nature-based solutions and carbon trading, along with green accounting and sustainability reporting, play a crucial role in reducing environmental impact and increasing corporate accountability. Supported by government regulations, these practices not only mitigate climate change but also offer long-term economic benefits and social value. It is recommended that mining companies adopt comprehensive green mining practices by integrating carbon offset strategies into long-term business models, supported by refined government regulations, enhanced stakeholder competencies through academic and professional training, further research on carbon offset impacts, and strong public-private collaboration to accelerate the transition toward a sustainable green mining industry.